Host and Parasite Evolution in a Tangled Bank. Issue 11 (November 2016) - Betts, Alex; Rafaluk, Charlotte; King, Kayla C.
Abstract : Most hosts and parasites exist in diverse communities wherein they interact with other species, spanning the parasite–mutualist continuum. These additional interactions have the potential to impose selection on hosts and parasites and influence the patterns and processes of their evolution. Yet, host–parasite interactions are almost exclusively studied in species pairs. A wave of new research has incorporated a multispecies community context, showing that additional ecological interactions can alter components of host and parasite fitness, as well as interaction specificity and virulence. Here, we synthesize these findings to assess the effects of increased species diversity on the patterns and processes of host and parasite evolution. We argue that our understanding of host–parasite interactions would benefit from a richer biotic perspective. Trends: Host–parasite research has traditionally been conducted in a pairwise species framework. Expanding investigations of host–parasite evolutionary interactions into more complex communities could illuminate patterns and processes occurring in natural systems. There has been a recent surge of research that has sought to incorporate increased biotic complexity in experimental designs, by including multiple species of hosts, parasites, or defensive mutualists. Such experiments have revealed the importance of biotic context in exploring the nature of evolutionary interactions and where they fall on the parasite–mutualist continuum. By combining evolutionary, ecological, and genomic approaches, researchers have begun to reveal the importance of feedbacks in communities and understanding how these interactions are influenced by the addition of biotic interactions.